Socio-Emotional Factors and the Succession Process in Family Firms - Arreola Bravo, Francisco Moisés; Niebla Zatarain, Juan Cayetano; Ramírez Martínez, Guillermo (CIENCIA ergo-sum; Vol 22 No 2 (2015): CIENCIA ergo-sum (July- October 2015), 2015)
This paper uses the Socio-Emotional Wealth view (sew) to build a conceptual model as a tool for understanding and analyzing relationships between socio-emotional wealth dimensions and succession process as well as next generation´s performance. Authors find that it exists a direct relationship between the level of participation of family members and the intention of transferring the business to the next generation. It is found that socio-emotional factors are determinant of the next generation's experience quality and performance.